2018
DOI: 10.1007/s40430-018-0986-y
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis and performance experiment of electric submersible pump with different diffuser vanes number

Abstract: Space diffuser is one of the most critical flow components in electric submersible pumps; its hydraulic design has the significant effects on the pump performance. In this paper, a typical electric submersible pump was chosen as the research object to study the influence of space diffuser vanes number, by means of numerical simulation and experimental test methods. Based on the same curve profile and same impeller, the diffuser vanes number was adjusted to three different schemes of 6, 7, and 8. Calculation do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Since the motor and pump were immersed in water, the motor output power (i.e., shaft power) could not be directly measured by a torque meter or dynamometer. Therefore, the motor loss analysis method was used to calculate the shaft power using a no-load test to determine the continuous loss [ 32 , 33 ]. The schematic diagram and test site of the pump test rig is shown in Figure 3 .…”
Section: Comparison Of the Predicted And Experimental Resultsmentioning
confidence: 99%
“…Since the motor and pump were immersed in water, the motor output power (i.e., shaft power) could not be directly measured by a torque meter or dynamometer. Therefore, the motor loss analysis method was used to calculate the shaft power using a no-load test to determine the continuous loss [ 32 , 33 ]. The schematic diagram and test site of the pump test rig is shown in Figure 3 .…”
Section: Comparison Of the Predicted And Experimental Resultsmentioning
confidence: 99%
“…In this study, the k- turbulence model along with PISO algorithm was chosen in numerical simulations. Many studies in the literature have found that the k- turbulence model best fits experimental measurements in centrifugal pumps with reverse pressure gradient and separations (Li et al, 2016, Zhou et al, 2018, Spence and Amaral-Teixeirab, 2008. Eddy viscosity in k- turbulence model based on two equations and Boussinesq Theorem:…”
Section: Solid Model Design Of the Pump And Numerical Setupmentioning
confidence: 94%
“…This trend is a result of significant developments in computer capacities, in parallel with the development of numerical solution methods in recent years. Accordingly, the literature studies on the subject, which include numerical and experimental processes together: (i) The relationship of geometric components with the flow field throughout the pump (Pei et al, 2016;Zhou et al, 2018;Yuanyi et al 2009;Shi et al 2013;Tao et al 2017), (ii) Reliability of numerical simulations in pump design (Yao et al 2016;Maitelli et al 2010;Derakhshan and Nourbersi 2008) and (iii) Effect of fluid viscosity on pump performance . It can be classified under three titles.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent decades, a lot of scholars have devoted themselves to the improvement of ESP performance. They have proposed abundant performance optimization methods including orthogonal optimization [3][4][5], numerical calculation [6][7][8][9], and neural network genetic algorithm [10,11] for the structural parameters like the angle of installation, the number of blades, and the wrap angle of the blade.…”
Section: Introductionmentioning
confidence: 99%